Cardiac involvement in Anderson-Fabry disease - Kampmann, Christoph; Baehner, Frank; Ries, Markus; Beck, Michael (Journal of the American Society of Nephrology, 2002)
Anderson-Fabry disease results from hereditary deficiency of the lysosomal enzyme α-galactosidase A. This disease is marked by progressive intracellular accumulation of globotriaosylceramide (Gb3) and digalactosylceramide, the major glycosphingolipid substrates of α-galactosidase A. Many cell